PEMBERDAYAAN ANAK REMAJA DALAM PENCEGAHAN KEHAMILAN USIA DINI DI SMA SWASTA SANTA MARIA TARUTUNG - Marni Siregar; Juana Linda Simbolon; Emilia Silvana Sitompul (JURNAL PENGABDIAN KEPADA MASYARAKAT BIDANG KESEHATAN, 2020)
Abstract Santa Maria Private High School, Tarutung Subdistrict, is a favorite SMA in North Tapanuli Regency where the location is located in an area that is easily accessible from other areas in North Tapanuli Regency. The large number of students and inadequate parental control because many are boarding can also result in susceptibility to premarital sexual behavior. The risk factors for adolescent sexual activity are lack of parental supervision and low environmental supervision so that boarding students are at risk of various forms of sexual activity.Prevent early pregnancy by providing information to adolescents to empower them to build values and skills that enable them to make responsible decisions to become sexually healthy adults. Counseling for adolescents about sex education is the most likely, especially to students in schools. Factors that influence adolescent sexual behavior include academic perspectives where adolescents with low achievement and low aspiration stages tend to be more likely to have sexual activity than adolescents with good performance in school so that by providing health education for all students both with low achievement and good achievement. understand the impact of premarital sex.Â Keywords: early pregnancy, empowerment, teenager